Sequencing, de novo assembly and annotation of a pink bollworm larval midgut transcriptome. Issue 1 (December 2016) - Tassone, Erica; Zastrow-Hayes, Gina; Mathis, John; Nelson, Mark; Wu, Gusui; Flexner, J.; Carrière, Yves; Tabashnik, Bruce; Fabrick, Jeffrey
Abstract Background The pink bollwormPectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) is one of the world's most important pests of cotton. Insecticide sprays and transgenic cotton producing toxins of the bacteriumBacillus thuringiensis (Bt) are currently used to manage this pest. Bt toxins kill susceptible insects by specifically binding to and destroying midgut cells, but they are not toxic to most other organisms. Pink bollworm is useful as a model for understanding insect responses to Bt toxins, yet advances in understanding at the molecular level have been limited because basic genomic information is lacking for this cosmopolitan pest. Here, we have sequenced, de novo assembled and annotated a comprehensive larval midgut transcriptome from a susceptible strain of pink bollworm. Findings Ade novo transcriptome assembly for the midgut ofP. gossypiella was generated containing 46, 458 transcripts (average length of 770 bp) derived from 39, 874 unigenes. The size of the transcriptome is similar to published midgut transcriptomes of other Lepidoptera and includes up to 91 % annotated contigs. The dataset is publicly available in NCBI and GigaDB as a resource for researchers. Conclusions Foundational knowledge of protein-coding genes from the pink bollworm midgut is critical for understanding how this important insect pest functions. The transcriptome data presented here represent the first large-scale molecular resource for this species, and may be used for deciphering relevant midgut proteins critical for xenobiotic detoxification, nutrient digestion and allocation, as well as for the discovery of protein receptors important for Bt intoxication.